EFFICACY OF SEVOFLURANE VERSUS PROPOFOL FOR INTUBATION WITHOUT USING NEUROMUSCULAR BLOCKERS IN CHILDREN UNDERGOING ELECTIVE SURGERY AT TERTIARY CARE HOSPITAL: http://doi.org/10.46536/jpumhs/2023/13.03.458 - Sidra Qureshi1 , Syeda Zehra Haque2 , Muhammad Waseem3 , Wajeeha Marium4 , Nafhan Najmi5 , Hussainy6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
BACKGROUND: The process of pediatric endotracheal intubation in the context of elective procedures presents distinct difficulties, as the selection of induction agents directly influences the resulting clinical results. Using neuromuscular blockers has inherent hazards, necessitating investigating other approaches to attain ideal intubation circumstances. The present research aimed to examine and compare the effectiveness of sevoflurane and propofol in pediatric intubation, particularly in the absence of neuromuscular blockers. OBJECTIVE: To compare the efficacy of Sevoflurane versus Propofol for intubation without using neuromuscular blockers in children undergoing elective surgeries at a tertiary care hospital. METHODS: A randomized controlled trial was conducted in the Department of Anesthesiology, Patel Hospital Karachi, over a period of six months. The research comprised a cohort of sixty-two pediatric patients aged 1 month to 5 years. These patients were categorized as ASA status I-II. The individuals in question were slated to undergo elective medical operations while under the effects of general anesthesia. The individuals were randomly assigned to receive either sevoflurane or propofol throughout the induction procedure. This study's primary outcome of interest was clinical effectiveness, which was assessed by evaluating intubation ratings. Moreover, several other attributes were recorded, including patient demographics, length of laryngoscopy, ASA classification, and incidences of adverse events. RESULTS: The sevoflurane group had a notably greater level of clinical efficacy, as seen by 75.8% of patients obtaining successful intubation, in contrast to the propofol group, where only 51.6% of patients achieved successful intubation p-value <0.001. A significant proportion of patients in both cohorts had favorable outcomes regarding intubation ratings, ranging from satisfactory to outstanding. The incidence of adverse effects, such as laryngospasm and the administration of succinylcholine, was infrequent and seen in a minority of the patient population. CONCLUSION: Sevoflurane has been identified as a more effective induction drug for pediatric intubation without neuromuscular blockers during elective surgical procedures. The promise of sevoflurane as an alternative to conventional muscle relaxants in pediatric anesthesia is indicated by its clinical efficacy and excellent safety profile. Additional multicenter trials should be conducted to verify these results and establish sevoflurane as the preferred option for pediatric intubation.